T Follicular Helper Cells Promote a Beneficial Gut Ecosystem for Host Metabolic Homeostasis by Sensing Microbiota-Derived Extracellular ATP - Perruzza, Lisa; Gargari, Giorgio; Proietti, Michele; Fosso, Bruno; D’Erchia, Anna Maria; Faliti, Caterina Elisa; Rezzonico-Jost, Tanja; Scribano, Daniela; Mauri, Laura; Colombo, Diego; Pellegrini, Giovanni; Moregola, Annalisa; et al. (Cell reports (Cambridge), 2017)
The ATP-gated ionotropic P2X7 receptor regulates T follicular helper (Tfh) cell abundance in the Peyer’s patches (PPs) of the small intestine; deletion of P2rx7, encoding for P2X7, in Tfh cells results in enhanced IgA secretion and binding to commensal bacteria. Here, we show that Tfh cell activity is important for generating a diverse bacterial community in the gut and that sensing of microbiota-derived extracellular ATP via P2X7 promotes the generation of a proficient gut ecosystem for metabolic homeostasis. The results of this study indicate that Tfh cells play a role in host-microbiota mutualism beyond protecting the intestinal mucosa by induction of affinity-matured IgA and suggest that extracellular ATP constitutes an inter-kingdom signaling molecule important for selecting a beneficial microbial community for the host via P2X7-mediated regulation of B cell help. [Display omitted] •P2X7 receptor activity in Tfh cells is important for shaping the gut microbiota•Control of secretory IgA by Tfh cells promotes a healthy gut ecosystem•Lack of P2X7 in Tfh cells results in selection of an obesogenic microbiota•Sensing of extracellular ATP by P2X7 in Tfh cells promotes host metabolic balance Gut commensals contribute to host metabolic homeostasis. ATP released by bacteria limits IgA secretion in the small intestine via the P2X7 receptor expressed in T follicular helper cells. Perruzza et al. show that this regulatory mechanism is important for shaping a diverse microbiota that promote host metabolic homeostasis.